PENGARUH PEMBERIAN PUPUK KANDANG AYAM DAN PUPUK N TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays L. Var Saccarata Sturt) - Ahmad ' Taufiq; Husna ' Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Sweet corn (Zea mays L. var Saccarata Sturt) is one type of plant that those fresh harvested and cultivated in the tropics. In the cultivation of sweet corn there are many things those need to be addressed such as soil fertility. Attempts to improve soil fertility can be done by providing organic fertilizer and inorganic fertilizer. One good organic fertilizer was chicken manure. While inorganic fertilizers needed include nitrogen (N). This study aimed to determine the effect of chicken manure and fertilizer N on the growth and yield of sweet corn (Zea mays L. Var Saccarata Sturt) and to get the best treatments. This research was conducted at the Experimental Farm, Faculty of Agriculture, University of Riau, Pekanbaru and held for 3 months ie in January to March 2016. The study was conducted experimentally using a randomized block design (RCBD) factorial and three replications. Factor 1: Provision of chicken manure: A1 = 10 tonnes/ha, A2 = 20 tonnes/ha and A3 = 30 tonnes/ha. Factor 2: Fertilizer Urea: W1 = 100 kg/ha, W2 = 200 kg/ha, W3 = 300 kg/ha and W4 = 400 kg/ha. Combination of Urea 400 kg/ha with chicken manure 20 ton/ha gave the highestyield in sweet corn with the the results of 9,153 kg/4,5m2 or equal to 20,340 tonnes/ha compared with a combination of urea 100 kg/ha with manure chicken 10 tons/ha is 7,321 kg/4,5m2, equivalent to 16,269 tonnes/ha, meaning that the difference has a                    4,071 ton/ha (20,01%).   Keywords: Sweet Corn, Urea Fertilizer and Manure Chicken